Composition of Defense Budget of the Directorate General of Defense Potential Republic of Indonesia and its Impact on the Defense Economy in Covid-19 Pandemic - Simanjuntak, Marimbun; Sundari, Sri; Hermawan, Adib; Haetami, Haetami (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study discusses the impact of the Covid-19 Pandemic on the Defense Budget of the Directorate General of Defense Potential of the Indonesian Ministry of Defense. This research is motivated by the existence of a Pandemic which has an impact on changes in the composition of the Defense Budget of the Directorate General of Defense Potential of the Ministry of Defense of the Republic of Indonesia. The results of this study indicate that the implementation of the Defense Budget of the Directorate General of Defense Potential of the Ministry of Defense of the Republic of Indonesia is not in accordance with what is planned in the strategic plan, this discrepancy indicates that due to the Covid-19 Pandemic which resulted in changes in the composition of the budget of the Directorate General of Pothan of the Ministry of Defense of the Republic of Indonesia, this has an impact on program implementation and the goal of the results to be achieved previously. Suggestions that become recommendations for input in this research are the existence of Special Funds in each Ministry/Institution that can be used for special things such as during the Covid-19 Pandemic so that it is hoped that activities that are a National Priority Scale can run well and so that the results of the activities are achieved. implemented to achieve the desired goals.